Into Africa - McDonnell, Peter (Zaner-Bloser, Inc.)
Africa is the second-largest continent on Earth. Hundreds of millions of people live in Africa. Africans speak about 500 different languages!...
Keywords: Juvenile Non-Fiction / Continent / Africa